A Simulation-based Optimization Model for the Vehicle Routing Problem with Bimodal Stochastic Travel Time Distribution. Issue 10 (2022) - Antit, Amina; Jaoua, Amel; Layeb, Safa Bhar; Triki, Chefi
Abstract: This paper proposes a simulation-based optimization model for solving a realistic delivery problem within an urban area that respects the customers' availability. Specifically, the originality of this work is to consider the bimodal realistic traffic pattern when solving the classic capacitated vehicle routing problem with time windows. Computational results have shown that under bimodal travel time distribution the routing solution changes considerately. Thus, this work emphasizes the need to fully integrate the traffic behavior when solving this class of routing problem with stochastic travel times. Furthermore, it highlights the easiness of such integration, when the routing problem is modeled and solved using this promising simulation-based optimization approach.